Comparative Study of Competency and Certification of Special Education Teachers in Various Countries - Puspasari, Asri Dwi; Widyastono, Herry (Journal of ICSAR, 2020)
Being a professional teacher must meet the competency standards set by the government. Special education teachers must also be professional because special education teachers must have specific competencies that teachers in public schools do not possess. This study aims to describe special education teachers' competence and certification in various countries, namely Indonesia, Malaysia, the Philippines, Thailand, and South Korea. Teacher certification is the process of giving educator certificates to teachers and has several competencies, namely: pedagogical competence, personality competence, social competence, and professional competence. In several countries such as Indonesia, Malaysia, Philippines, Thailand, and South Korea, the special education teacher certification program must have a Bachelor of Education academic qualification, have an educator certificate by following the available programs, and pass a field competency test.